Process intensification of hydrogen production by catalytic steam methane reforming: Performance analysis of multilayer perceptron-artificial neural networks and nonlinear response surface techniques - Ayodele B.V.; Alsaffar M.A.; Mustapa S.I.; Adesina A.; Kanthasamy R.; Witoon T.; Abdullah S. (Institution of Chemical Engineers, 2023)
Chemical activation; Errors; Gradient methods; Hydrogen production; Hyperbolic functions; Mean square error; Methane; Nonlinear analysis; Sensitivity analysis; Steam; Steam reforming; Surface properties; Activation functions; Artificial neurons; Gradient-descent; Multilayers perceptrons; Network response; Non-linear response; Nonlinear response surface technique; Performance; Process intensification; Response surface techniques; Multilayer neural networks